The Effect of the Combination of Tempeh Flour and Kepok Banana Peel Flour (Musa paradisiaca Linn.) on the Chemical and Organoleptic Quality of Butter Cookies - Nadya Allen Liefena; Bambang Sigit Sucahyo; Fadjar Kurnia Hartati (Green Publisher Indonesia, 2026)
Butter cookies are one of the most popular food products due to their crispy texture and distinctive flavor. Tempeh flour, as a source of plant-based protein, and kepok banana peel flour (Musa paradisiaca Linn.), as a source of dietary fiber, have significant potential to be utilized as functional ingredients in cookie product development. This study aimed to determine the effect of combining tempeh flour and kepok banana peel flour on the chemical and organoleptic quality of butter cookies. This research employed a laboratory experimental method using a Completely Randomized Design (CRD) with one factor, namely variations in flour combination concentrations: T1P1 (90% : 10%), T2P2 (80% : 20%), T3P3 (70% : 30%), and T4P4 (50% : 50%), each with three replications. The observed variables included chemical quality (moisture content, ash content, protein content, and fiber content) and organoleptic quality (color, aroma, taste, texture, and overall acceptability) of butter cookies. Parametric data were analyzed using Analysis of Variance (ANOVA) with the assistance of Statistical Product and Service Solutions (SPSS) software, while non-parametric data were analyzed using Duncan’s Multiple Range Test (DMRT). Based on the effectiveness test using the De Garmo method, treatment T2P2 was selected as the best treatment with a total score of 0.626, producing the most optimal physicochemical and organoleptic characteristics.